Are circle hooks effective management measures in the pelagic longline fishery for sharks in the Gulf of Gabès?. Issue 6 (7th March 2020) - Saidi, Bechir; Echwikhi, Khaled; Enajjar, Samira; Karaa, Sami; Jribi, Imed; Bradai, Mohamed N.
Abstract: This study evaluated the circle hook use as a tool for shark management in the pelagic longline fishery in the Gulf of Gabès. The usual J‐hook No. 2 with 10° offset, which has been traditionally used by the fishery, was compared to the 18/0 non‐offset circle hook in an alternating fashion along the main line. In total, 22 experimental longline sets were deployed through the shark fishing seasons of 2016 and 2017 to examine the effects of hook types on the catch composition, the catch rates, the hooking location, and the status at haulback. The catch composition differed significantly among hook types. Moreover, an overall increase in catch rates for the main species, the sandbar shark Carcharhinus plumbeus, and the shortfin mako shark Isurus oxyrinchus, was observed when using circle hooks. There was no size‐selective effect of circle hooks for the common species. The circle hooks were not effective at reducing at‐haulback mortality of sandbar shark. Conversely, shortfin mako and smooth‐hound shark Mustelus mustelus showed significantly lower relative mortality at haulback with circle hooks than with J‐hooks. Furthermore, circle hooks were more frequently hooked externally than the J‐hooks for the three shark species. Results demonstrated that the use of 18/0 non‐offset circle hooks in the pelagic shark longline fishery can reduce mortality at haulback for some species without any benefit for the dominant species, the sandbar shark. Overall, it is difficult to promote the adoption of the use of circle hooks as a management measure in this specialized fishery. Management measures focusing on fishing effort controls, fishing closures in critical habitats, and size limits could have significant benefits for the conservation of shark species and may help to improve the sustainability of the shark fishery in the Gulf of Gabès.